2011
DOI: 10.1002/marc.201100243
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Hydrophilization of Nanoporous 1,2‐PB by Thiol‐ene Photochemistry

Abstract: We present an efficient method for functionalizing the large polymer-air interface of a gyroid nanoporous polymer. The hydrophilicity of nanoporous cross-linked 1,2-polybutadiene is tuned by thiol-ene photo-grafting of mercaptosuccinic acid or sodium 2-mercaptoethanesulfonate. The reaction is monitored by FT-IR, UV-Vis, contact angle, and gravimetry. Overall quantum yields are calculated for the two thiol-ene "click" reactions in nano-confinement, neatly revealing their chain-like nature. Top-down photolithogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…We previously reported that the originally hydrophobic membranes can be turned into hydrophilic via UV photooxidation 20 or thiolÀene photochemistry. 21 Water can spontaneously and exclusively fill the hydrophilized nanopores. As a result, the hydrophilized nanopores are permeable to the diffusing species in aqueous solutions, while no diffusion happens in the unmodified pores.…”
mentioning
confidence: 99%
“…We previously reported that the originally hydrophobic membranes can be turned into hydrophilic via UV photooxidation 20 or thiolÀene photochemistry. 21 Water can spontaneously and exclusively fill the hydrophilized nanopores. As a result, the hydrophilized nanopores are permeable to the diffusing species in aqueous solutions, while no diffusion happens in the unmodified pores.…”
mentioning
confidence: 99%
“…In the past few years, colossal advances have been made for the former strategy, due to the presence of highly active pendent vinyl substituents. [16][17][18][19][20][21][22] For instance, Mecking, Ndoni, et al, presented efficient functionalization of sPB via thiol-ene reaction, through which various types of functional groups, including ester, L-cysteine, carboxylic acid were successfully introduced; [23][24][25] Linford and Tang reported hydrosilation and hydrozirconation of 1,2-polybutadiene (1,2-PB) by Si-H and Zr-H reagents, and provided a platform for accessing diversied functional 1,2-PBs. 26,27 Despite of the facility and efficiency in these reports, all of them were built on the sacrice of pendent double bonds, which might cause irreversible damage to the inherent nature of sPB, such as crystallinity, 28 molecular weights, 16 and even causing cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting strategy to change the surface chemistry of originally hydrophobic membranes has been recently proposed by Ndoni et al who were able to hydrophilize the nanopores of 1,2-PB membranes via UV-photooxidation [71] or thiol-ene photochemistry [72].…”
Section: Tunability Of Surface Propertiesmentioning
confidence: 99%